Different phenotypes of polycystic ovary syndrome in Turkish women: clinical and endocrine characteristics. (26th July 2013) - Ates, Seda; Sevket, Osman; Sudolmus, Sinem; Dane, Banu; Ozkal, Fulya; Uysal, Omer; Dansuk, Ramazan
Abstract: This study presents the differences in clinical, endocrine and metabolic parameters among different polycystic ovary syndrome (PCOS) phenotypes in Turkish women. Four hundred and ten women with PCOS were evaluated, while 97 healthy women served as controls. PCOS were defined by oligo-anovulation (OA), hyperandrogenism (HA) and polycystic ovaries on ultrasound (PCO). Patients were subdivided into four phenotypes: OA + HA + PCO (phenotype 1), OA + HA (phenotype 2), HA + PCO (phenotype 3), OA + PCO (phenotype 4). Phenotypes 1–4 were present in 47.1%, 13.2%, 21.2% and 18.5% of patients, respectively. They were also divided into three groups according to the BMI (<25 kg/m 2 ; 25≤ and ≤30 kg/m 2 ; and >30 kg/m 2 ). ANOVA and Tukey post-hoc HSD tests were used. The LH levels and LH/FSH ratio were higher in phenotype 1 and 2 than phenotype 3. The LDL-C levels were higher in women with phenotype 1 and 4 than in women with phenotype 2. Women with BMI <25 kg/m 2 had higher levels of LH, LH/FSH ratio, and the HDL-C than other two groups. The levels of TG, LDL, fasting insulin and HOMA-IR increased with increasing BMI in four phenotypes. Results suggest that obesity seems to be the primary cause of metabolic disturbances in PCOS women.